Effects, consequences and regulation of surrogated maternity - Regalado Torres, María Desirée (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
On the one hand, for many people subrogated gestation means a great advantage in assisted reproduction techniques because of it is an alternative for those who cannot conceive naturally. On the other hand, for some people it means sexual exploitation of women, who are treated as an object and manipulated with the intention of granting a wish of people who want to become parents, and all this is part of a contractual and disproportionate liberalism. This essay shows the ethical and legal inconvenients caused by subrogated maternity to the expectant mother, the child and the recipient parents. Besides, the controversial debate in relation to the necessity of updating the term maternity will be analysed as a consequence of the socioeconomic development that has had subrogated maternity due to the abscence of prohibitions or a regulation in many countries.